2009
DOI: 10.3109/01480540903130716
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of influence of carmustine and new proline analog of nitrosourea on antioxidant system in breast carcinoma cells (MCF-7)

Abstract: The high toxicity and low selectivity of carmustine restrict its application in anticancer therapy. Therefore, proline analogs of nitrosourea have been synthesized to obtain compounds whose action on neoplastic cells is characterized by higher selectivity. The present studies have aimed at examining the influence of carmustine and a new proline analog of nitrosourea on the redox system of fibroblasts and breast cancer cells (MCF-7). Carmustine and the proline analog of nitrosourea caused an increase in hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Because tyrosines that are post-translationally modified by nitrating oxidants, brominating oxidants, and chloramination oxidants produced from macrophages, neutrophils or eosinophils to form nitrotyrosine, bromotyrosine and chlorotyrosine respectively, have relevance to breast cancers (26)(27)(28)(29)(30)(31)(32). For example, hypochlorous acid/hypochlorite adducts have been reported for breast cancer (33)(34)(35)(36). Our studies suggest that circulating PTM levels can be used as a biomarker for endothelial cell dysfunction, which is of concern in several human diseases.…”
Section: Oxidation Biomarkers For Early Breast Cancermentioning
confidence: 72%
“…Because tyrosines that are post-translationally modified by nitrating oxidants, brominating oxidants, and chloramination oxidants produced from macrophages, neutrophils or eosinophils to form nitrotyrosine, bromotyrosine and chlorotyrosine respectively, have relevance to breast cancers (26)(27)(28)(29)(30)(31)(32). For example, hypochlorous acid/hypochlorite adducts have been reported for breast cancer (33)(34)(35)(36). Our studies suggest that circulating PTM levels can be used as a biomarker for endothelial cell dysfunction, which is of concern in several human diseases.…”
Section: Oxidation Biomarkers For Early Breast Cancermentioning
confidence: 72%
“…Because tyrosines that are post-translationally modified by nitrating oxidants, brominating oxidants, and chloramination oxidants produced from macrophages, neutrophils or eosinophils to form nitrotyrosine, bromotyrosine and chlorotyrosine respectively, have relevance to breast cancers (17)(18)(19)(20)(21)(22)(23). For example, hypochlorous acid/hypochlorite adducts have been reported for breast cancer (24)(25)(26)(27). Our studies suggest that circulating PTM levels can be used as a biomarker for endothelial cell dysfunction, which is of concern in several human diseases.…”
Section: Body Develop and Validate Ptm-elisa Microarraymentioning
confidence: 93%
“…According to the clinical observation, CENUs can also lead to the generation of secondary tumors after the treatment. However, the carcinogenic mechanisms of CENUs are still poorly understood [7]. Reports showed that the pathogenetic mechanism of secondary tumors during therapy due to formation of ICLs [8].…”
Section: Introductionmentioning
confidence: 99%